ChemInform Abstract: Overview of the Characteristic Features of the Magnetic Phase Transition with Regards to the Magnetocaloric Effect: The Hidden Relationship Between Hysteresis and Latent Heat. Issue 30 (July 2016) - Morrison, Kelly; Cohen, Lesley F.
Abstract: Review: 36 refs.